Exploring Teaching and Learning of Critical Thinking in Private Schools in Dubai - Waqas, Sumiya (2019)
Critical thinking is one of the most desirable skills of the 21st century which is required to meet the challenges associated with today’s modern world of technology. The current study aims to explore and analyze the various teaching methods and strategies utilized by the teachers in private school in Dubai. It focuses on promoting critical thinking skills amongst students. The current research adopts a mix method approach in the research design whereby teachers and students of grades 4 and 5 of a Dubai private school participated. A quantitative research method utilizing teacher and student questionnaires were used and analyzed using SPSS software. Qualitative research methods are utilized to support the results obtained by quantitative methods which includes various classroom observations of grades 5 and 6. Results of the study depict that various teaching strategies are being utilized by private school teachers in Dubai to promote critical thinking amongst students. These teaching methods and strategies include group discussion, brain storming, encouraging students to ask questions and share their viewpoint along with cultivating a sociological classroom learning environment that is conducive for learning critical thinking skills. The results depict that teacher’s teaching strategies have a positive relation with student’s learning methods and increasing teaching strategies also enhances student’s learning. In addition, no significant differences were observed in the teaching strategies and methods in different subject classes and grades.